Oral Submucous Fibrosis – The Indian Scenario: Review and Report of Three Treated Cases - Kamala Rawson; Ruchika K Prasad; Admaja K Nair; Juliet Josephine (Journal of Indian Academy of Oral Medicine and Radiology, 2017)
Oral submucous fibrosis (OSF) is a premalignant condition mainly associated with the practice of chewing betel quid containing areca nut, a habit common among south Asian people. It is characterized by inflammation, increased deposition of submucosal collagen, and formation of fibrotic bands in the oral and paraoral tissues, which increasingly limit mouth opening. In this paper, we review literature on OSF and the different stages of the disease to help dentists make an early diagnosis and reduce the morbidity and mortality associated with this condition. We also present three cases after treatment with biweekly intralesional injections which resulted in improvement of the subjective symptoms.